DPEP1 Balance GSH Involve in Cadmium Stress Response in Blood Clam Tegillarca granosa - Song, Danli; Lin, Zhihua; Yuan, Yongjun; Qian, Guang; Li, Chenghua; Bao, Yongbo (Frontiers in Physiology, 2018)
The blood clam, Tegillarca granosa, is a benthic filter feeder with a strong capacity to accumulate and tolerate cadmium (Cd). In our previous study, DPEP1 was shown to be significantly up-regulated under Cd stress based on proteomic analysis. To investigate whether DPEP1 is involved in Cd-induced response, the function of DPEP1 in T. granosa was investigated by integrated molecular and protein approaches. Rapid amplification cDNA end (RACE) assay was established to achieve the complete cDNA sequence of DPEP1 from T. granosa. The full-length cDNA of DPEP1 was 1811 bp, and it contained a 1359-bp open reading frame (ORF), including a 22-amino acid signal peptide. qRT-PCR analysis revealed that DPEP1 was expressed in all examined tissues with the highest expression in gills. At the same time, we investigated DPEP1 gene expression changes after Cd stress at different time points over 96 h. We found that the expression of DPEP1 increased upon initial Cd stress, then it was inhibited, and finally, it was maintained at a low level. Moreover, recombinant DPEP1 showed that higher glutathione (GSH) hydrolysis activity in the temperature range of 30-40 °C, and its maximum activity was at pH=6. Additionally, the results of immunohistochemistry also confirmed that DPEP1 protein was expressed in all test tissues with the highest expression in gills. In addition, the protein expression of DPEP1 by immunohistochemistry was consistent with qRT-PCR results. These results suggested that DPEP1 is probably involved in Cd-induced response by balancing GSH.